Punitiveness and Devaluation among Social Work Gatekeepers - Johanna Pangritz; Wilhelm Berghan (Social Work & Society, 2020)
This paper analyses the connection between a punitive educational orientation and different negative prejudices in the context of group-focused enmity. While punitiveness is a very rough and undefined term, it is the subject of lively debate within social work. Here, punitiveness is often understood as a move away from the former welfare state ideal by giving preference to harsh punishment rather than practices of resocialization. The results of a quantitative survey (n = 178) of future street-level bureaucrats in the social field show that a punitive educational orientation is positively related to prejudices. This has implications for theorizing on the role of punitiveness in intergroup conflict and especially for practical social work, as it devalues certain social groups that are addressees of social work through punitive practice. This also includes assumptions about citizenship, as statements are made about who belongs and who does not.